Analysis of Labor Welfare Policies and their Impact on the University Community in Rosario, Sinaloa, Mexico. - Hernández Osuna, Adolfo Arturo (Universidad Francisco de Paula Santander, 2024)
The work well-being policies implemented in the institution have a positive, although uneven, impact on different groups within the community. In general terms, it was observed that administrative staff present higher levels of satisfaction in relation to well-being policies, compared to with teachers and students, however, it was identified that communication and accessibility to certain programs are insufficient, especially among students, who are largely unaware of the benefits available. Likewise, the research used a mixed methodology, which combined quantitative approaches and qualitative to obtain a comprehensive vision of the impact of workplace well-being policies. As a result, 72% of the administrative staff and 65% of the teaching staff expressed satisfaction with the well-being policies, however, only 40% of the students stated that they were aware of these policies and how to access them; A correlation was observed between satisfaction with wellness policies and an increase in productivity, with 68% of respondents stating that wellness initiatives contribute to improving their performance.